Prevention of arterial and venous thrombotic events in symptomatic peripheral arterial disease patients after lower extremity revascularization in the VOYAGER PAD trial: Dual anticoagulant/antiplatelet regimen vs antiplatelet therapy alone. (7th March 2022) - Berkowitz, Scott D.; Bauersachs, Rupert M.; Szarek, Michael; Nehler, Mark R.; Debus, E. Sebastian; Patel, Manesh R.; Anand, Sonia S.; Capell, Warren H.; Hess, Connie N.; Hsia, Judy; Leeper, Nicholas J.; Brasil, David; et al.
Abstract: Background: Vascular disease burden after lower extremity revascularization (LER) comprises more than the first event, more vascular beds than the local arteries, and more than one clinical event type. Objectives: Assess total arterial and venous thrombotic burden after LER for symptomatic peripheral artery disease (PAD) and effect of low‐dose anticoagulation added to low‐dose antiplatelet therapy. Patients/Methods: VOYAGER PAD randomized 6564 symptomatic PAD patients undergoing LER to rivaroxaban 2.5 mg twice‐daily or placebo on aspirin background. Marginal proportional‐hazards models used to generate treatment hazard ratios and associated 95% CIs for first and total events; non‐thrombotic deaths treated as competing terminal events. Incidence rates calculated as number of events per 100 patient‐years follow‐up. Results: Over 2.5 years (median), first and total thrombotic event rates: 7.1 and 10.3 events/100 patient‐years, respectively, in placebo group. Two‐thirds (925/1372) of total thrombotic events (arterial 95%, venous 5%) were nonfatal first events. Nearly one‐third of patients with first event had a second arterial or venous thrombotic event. Rivaroxaban plus aspirin reduced first and total arterial and venous thrombotic events to 5.4 and 7.9 events/100 patient‐years, respectively, a reduction in total thrombotic events over aspirin of 23% (HR: 0.77, 95%CI: 0.67–0.89, p  = .0005), preventing 6.1 total arterial and venous thrombotic events at 3 years. Conclusions: Assessing total arterial and venous thrombotic events, not just first events, provides more complete information about disease burden and absolute on‐treatment impact. Following LER, judicious modulation of more than one coagulation pathway can provide broader benefit than intensifying inhibition of one hemostatic system component.